2018
DOI: 10.1007/s00464-018-6236-7
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted laparoscopic groin hernia repair: observational case-control study on the operative time during the learning curve

Abstract: Robotic TAPP was associated with a rapid reduction in operative time during our learning curve and afterwards the operative time to perform a robotic TAPP equals the operative time to perform a laparoscopic TAPP, both for unilateral and for bilateral groin hernia repairs. No complications related to the introduction of robotic-assisted laparoscopic groin hernia repair were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 15 publications
2
65
0
2
Order By: Relevance
“…The plateau of the LC for both laparoscopic TAPP and TEP procedures varies between 13 and 65 cases. 6,[14][15][16][17] The European Hernia Society guidelines state that the TAPP and totally extra peritoneal inguinal hernia repair LCs peak after experiencing 50-100 cases, with the first 30-50 cases having the highest incidence of complications. 18 Bansal et al reported that the average number for stabilization of the LC was 13 operations for laparoscopic TEP and TAPP.…”
Section: Discussionmentioning
confidence: 99%
“…The plateau of the LC for both laparoscopic TAPP and TEP procedures varies between 13 and 65 cases. 6,[14][15][16][17] The European Hernia Society guidelines state that the TAPP and totally extra peritoneal inguinal hernia repair LCs peak after experiencing 50-100 cases, with the first 30-50 cases having the highest incidence of complications. 18 Bansal et al reported that the average number for stabilization of the LC was 13 operations for laparoscopic TEP and TAPP.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, simultaneous repair of groin hernia can always be repaired quickly and easily. Therefore, groin hernia repair has rapidly gained popularity in the past decade, especially during a robot‐assisted radical prostatectomy, which potentially increases the incidence of groin hernias after surgery . However, whether we really need a surgical robot just for repairing a simple groin hernia is still questionable due to its higher cost, longer operative time, and uncertainty about its clinical benefits …”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic groin hernia repairs are commonly carried out via two standard approaches, either trans‐abdominal pre‐peritoneal (TAPP) repair or total extra‐peritoneal (TEP) repair. In the robotic era, most of the reported robot‐assisted techniques were performed using the TAPP approach, except in very limited case reports of simultaneous TEP repair during a robot‐assisted radical prostatectomy . Although these two standardized laparoscopic approaches for groin hernia repair are comparable in their long‐term clinical outcomes, the TAPP approach was associated with more surgical complications and seroma formation than was the TEP approach in a large‐scale population‐based study …”
Section: Introductionmentioning
confidence: 99%
“…Recently minimally invasive surgery (MIS) for inguinal hernia repair has become the procedure of choice for surgeons that previously favored an open anterior approach [8]. They are utilizing a robotic transabdominal pre-peritoneal approach (TAPP) instead of a pure laparoscopic approach [9,10].…”
mentioning
confidence: 99%
“…Previously surgeons had to learn the anatomy of the posterior approach and the details of the repair as well as had to master the laparoscopic skills required to safely complete the repair. For many surgeons the robotic platform has made this much easier and has initiated the recent rapid growth in MIS inguinal hernia repair [8][9][10].…”
mentioning
confidence: 99%